A Novel Antidipteran Bacillus thuringiensis Strain: Unusual Cry Toxin Genes in a Highly Dynamic Plasmid Environment - Fayad, Nancy (Appl Environ Microbiol, 2021)
Bacillus thuringiensis has emerged as a major bioinsecticide on the global market. It offers a valuable alternative to chemical products classically utilized to control pest insects. Despite the efficiency of several strains and products available on the market, the scientific community is always on the lookout for novel toxins that can replace or supplement the existing products. In this study, H3, a novel B. thuringiensis strain showing mosquitocidal activity, was isolated from Lebanese soil and characterized in vivo at genomic and proteomic levels. H3 parasporal crystal is toxic on its own but displays an unusual killing profile with a higher 50% lethal concentration (LC(50)) than the reference B. thuringiensis serovar israelensis crystal proteins. In addition, H3 has a different toxicity order: it is more toxic to Aedes albopictus and Anopheles gambiae than to Culex pipiens. Whole-genome sequencing and crystal analysis revealed that H3 can produce 11 novel Cry proteins, 8 of which are assembled in genes with an orf1-gap-orf2 organization, where orf2 is a potential Cry4-type crystallization domain. Moreover, pH3-180, the toxin-carrying plasmid, holds a wide repertoire of mobile genetic elements that amount to ca. 22% of its size., including novel insertion sequences and class II transposable elements. Two other large plasmids present in H3 carry genetic determinants for the production of many interesting molecules—such as chitinase, cellulase, and bacitracin—that may add up to H3 bioactive properties. This paper therefore reports a novel mosquitocidal Bacillus thuringiensis strain with unusual Cry toxin genes in a rich mobile DNA environment. IMPORTANCE Bacillus thuringiensis, a soil entomopathogenic bacterium, is at the base of many sustainable eco-friendly bioinsecticides. Hence stems the need to continually characterize insecticidal toxins. H3 is an antidipteran B. thuringiensis strain, isolated from Lebanese soil, whose parasporal crystal contains 11 novel Cry toxins and no Cyt toxins. In addition to its individual activity, H3 showed potential as a coformulant with classic commercialized B. thuringiensis products, to delay the emergence of resistance and to shorten the time required for killing. On a genomic level, H3 holds three large plasmids, one of which carries the toxin-coding genes, with four occurrences of the distinct orf1-gap-orf2 organization. Moreover, this plasmid is extremely rich in mobile genetic elements, unlike its two coresidents. This highlights the important underlying evolutionary traits between toxin-carrying plasmids and the adaptation of a B. thuringiensis strain to its environment and insect host spectrum.